2020
DOI: 10.1186/s41935-020-00184-5
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of evidence presentation in court: an insight into the practice of crime scene examiners in England, Wales and Australia

Abstract: Background: The ability to present complex forensic evidence in a courtroom in a manner that is fully comprehensible to all stakeholders remains problematic. Individual subjective interpretations may impede a collective and correct understanding of the complex environments and the evidence therein presented to them. This is not fully facilitated or assisted in any way with current non-technological evidence presentation methods such as poor resolution black and white photocopies or unidimensional photographs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…In [7], the challenges that crime scene specialists face when presenting complex forensic evidence in court were investigated. This study highlighted the utilization of modern techniques, such as 360° imagery and laser scanning to document crime scenes.…”
Section: B Related Workmentioning
confidence: 99%
“…In [7], the challenges that crime scene specialists face when presenting complex forensic evidence in court were investigated. This study highlighted the utilization of modern techniques, such as 360° imagery and laser scanning to document crime scenes.…”
Section: B Related Workmentioning
confidence: 99%
“…Digital photography in the investigation process is widely used in forensic analysis, cyber-crime or fraud [1], medical examination [12], forensic medical [13], crime scene investigation [6] and so on. According to [3], it has been around two decades since digital photography has been used in forensic investigation.…”
Section: Review Stage Digital Photography In Investigationmentioning
confidence: 99%
“…Crime scene photographs during the investigation process will be selected and included in the investigation papers for the prosecution process. However, according to [6], the traditional printing method still has a gap, often losing clarity and details, making it more challenging to interpret what they are seeing. Further, [6] suggested that the court must be better equipped with technology which could present the digital evidence during trial because although high end photography technologies were used by the crime scene officers in collecting the evidence, they were hindered from satisfactorily displaying the evidence due to lack of technology in court.…”
Section: E Relevency Digital Photography For Investigation Purposementioning
confidence: 99%
See 2 more Smart Citations